THE USE OF INSTAGRAM IN IMPROVING STUDENTS’ SKILL OF WRITING PROCEDURE TEXTS - Dwi Sulistyorini; Yusi Rahmawati (Universitas Muhammadiyah Semarang, 2019)
This research was a study which attempted to explain how effective the use of Instagram in improving students’ skill of writing procedure texts is, and to explain the factors that make Instagram improves students’ skill of writing procedure texts. This study used quasi-experimental. The subjects of the study were the 53 batch students of 4th semester of Technical Department of Politeknik Bumi Akpelni. There were two groups in this study, TB as the control group and TC as the experimental group, in each group there was 24 students. The control group was taught by using conventional method, while the experimental group was taught by using Instagram as a medium. The resultanalysis of the quantitative data shows that the mean scores of the experimental group increases from 64.13 to 82.45. The result indicates that the working hypothesis is accepted. It means that the there is significant difference between students who were taught by using Instagram and those who were taught by using conventional method. In addition, the analysis of the questionnaire shows that 51.61% of the students agree that the implementation of Instagram assists their writing. Therefore, the analysis reveals that Instagram is effective in teaching writing procedure text.